Cubature formula for approximate calculation of integrals of two-dimensional irregular highly oscillating functions - Mezhuyev, Vitaliy; Lytvyn, Oleg M.; Nechuiviter, Olesia; Pershyna, Yulia; Lytvyn, Oleg O.; Keita, Kateryna (University Politehnica of Bucharest, 2018)
The paper presents a new method for the calculation of integrals of two-dimensional irregular highly oscillatory functions for the case when information about functions is given on sets of lines. Estimation of the proposed method is done for the class of differentiable functions